Small family businesses: Innovation, risk and value - Samir Harith; Ruth Helen Samujh (Journal of Risk and Financial Management, 2020)
This article reviews the literature and applies principal-to-principal (PP) conflict theory to small family based businesses. The lack of accurate measurement and communication of risk leading to issues with innovation, is the primary cause of PP agency costs. Careful analysis of the risk levels reflected in the cost of debt and opportunity cost of equity provides a theoretically robust and empirically estimable process for ascertaining the true PP agency cost. Awareness of the constraining governance structures and the suggested method, based on the cost of capital, to assess small business risk can assist SME owners and financiers to SMEs to promote business efficiency and innovation.
Keywords: 330; cost of equity; family business; governance; principal-principal agency conflict; risk